Diskusi Penanganan Limbah Tahu dengan Pengusaha Tahu Kuning Balige Kabupaten Toba Sumatera Utara - Posma Sariguna Johnson Kennedy (Institut Teknologi dan Bisnis Semarang, 2023)
Yellow tofu, a valuable soybean-based product, plays a crucial role in providing plant-based protein. However, the tofu industry faces environmental challenges related to waste management. Community engagement activities were conducted by visiting the only yellow tofu industry in Balige, located in the Tambunan Sunge Village, Balige Subdistrict, Toba Regency. This discussion explores waste management practices in the Balige yellow tofu industry, emphasizing the need to reduce odor, clarify color, and decrease waste turbidity. By addressing these environmental concerns and empowering the local community, especially in the Lake Toba Tourism Area, we aim to promote sustainable growth in the yellow tofu industry.